Receptor Tyrosine Kinases in Osteosarcoma Treatment: Which Is the Key Target? - Tian, Zhichao; Niu, Xiaohui; Yao, Weitao (Frontiers in Oncology, 2020)
Recent clinical trials have shown several multi-target receptor tyrosine kinase inhibitors (TKIs) to be effective in the treatment of osteosarcoma. However, these TKIs have a number of targets, and it is yet unclear which of these targets has a key role in osteosarcoma. In this review, we first summarize the TKIs that were studied in clinical trials registered on ClinicalTrials.gov. Further, we compare and discuss the targets of these TKIs. We found that TKIs with promising therapeutic effect for osteosarcoma include apatinib, cabozantinib, lenvatinib, regorafenib, and sorafenib. The key targets for osteosarcoma treatment may include VEGFRs and RET. The receptor tyrosine kinases (RTKs) MET, IGF-1R, AXL, PDGFRs, KIT, and FGFRs might be relevant but unimportant targets for osteosarcoma treatment. Inhibition of one type of RTK is not effective in the treatment of osteosarcoma. It is necessary to inhibit several relevant RTKs simultaneously to achieve a breakthrough in osteosarcoma treatment. This review provides comprehensive information on TKI targets relevant in osteosarcoma treatment, and it will be useful for further research in this field.